2016
DOI: 10.1371/journal.pone.0159089
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus Middle Protein Enhances IL-6 Production via p38 MAPK/NF-κB Pathways in an ER Stress-Dependent Manner

Abstract: During hepatitis B virus (HBV) infection, three viral envelope proteins of HBV are overexpressed in the endoplasmic reticulum (ER). The large S protein (LHBs) and truncated middle S protein (MHBst) have been documented to play roles in regulating host gene expression and contribute to hepatic disease development. As a predominant protein at the ultrastructural level in biopsy samples taken from viremic patients, the role of the middle S protein (MHBs) remains to be understood despite its high immunogenicity. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 38 publications
2
15
0
Order By: Relevance
“…After a literature review, we found that our VZV IL-6 data were most similar to a description of elevated IL-6 following hepatitis B infection [30]. During hepatitis B infection, dysregulated production of the viral surface proteins leads to their retention in the ER with subsequent ER stress.…”
Section: Discussionsupporting
confidence: 77%
“…After a literature review, we found that our VZV IL-6 data were most similar to a description of elevated IL-6 following hepatitis B infection [30]. During hepatitis B infection, dysregulated production of the viral surface proteins leads to their retention in the ER with subsequent ER stress.…”
Section: Discussionsupporting
confidence: 77%
“…Many members of this family are reported to be involved in the HBV infection. IL-6 expression is upregulated by hepatitis B virus core antigen and middle S antigen via p38 MAPK/NF-κB pathways 19 20 . Meanwhile, serum IL-23 level in HBeAg-positive HBV infection patients before therapy could be used to predict the therapeutic response to interferon (IFN) 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Although environmental factors may play an important role in the pathogenesis and course of pemphigus, the contribution of viral infections to the disease remains unclear ( 72 ). Nonetheless, it has been reported that a hepatitis B virus envelope protein is capable of activating the p38 MAPK and NFĸB pathways in an ER stress-dependent manner ( 73 ), being therefore an example of how viral factors could directly contribute to a connected ER stress induction and p38 MAPK activation. Altogether, by adding ER stress to the understanding of pemphigus pathogenesis, an entirely new set of hypotheses and connections can be made in the context of the signaling pathways activated in the disease.…”
Section: The Emerging Role Of Er Stress In Pemphigusmentioning
confidence: 99%